2012
DOI: 10.4132/koreanjpathol.2012.46.4.382
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Renal Cell Carcinoma of Different Histological Subtypes in Autosomal Dominant Polycystic Kidney Disease

Abstract: Renal cell carcinoma (RCC) in autosomal dominant polycystic kidney (ADPKD) is rare. To date, 54 cases of RCC in ADPKD have been reported. Among these, only 2 cases have different histologic types of RCC. Here we describe a 45-year-old man who received radical nephrectomy for multifocal RCC with synchronous papillary and clear cell histology in ADPKD and chronic renal failure under regular hemodialysis. The case reported herein is another example of the rare pathological finding of RCC arising in a patient with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…While there is a much higher incidence of ESRD development in ADPKD patients, and ESRD leads to higher RCC risk, the data obtained at our institution supports the hypothesis that ADPKD patients still demonstrate higher rates of RCC than would be expected by ESRD alone. Furthermore, RCC in ADPKD patients develops at much younger ages (average 47 years) and is often bilateral (29%) and multicentric (25%) [12]. These rates are significantly higher than those found in sporadic RCC development, with 61 years being their median onset, 2% -6% are bilateral, and only 5% are multicentric [12] [13] [22].…”
Section: Discussionmentioning
confidence: 99%
“…While there is a much higher incidence of ESRD development in ADPKD patients, and ESRD leads to higher RCC risk, the data obtained at our institution supports the hypothesis that ADPKD patients still demonstrate higher rates of RCC than would be expected by ESRD alone. Furthermore, RCC in ADPKD patients develops at much younger ages (average 47 years) and is often bilateral (29%) and multicentric (25%) [12]. These rates are significantly higher than those found in sporadic RCC development, with 61 years being their median onset, 2% -6% are bilateral, and only 5% are multicentric [12] [13] [22].…”
Section: Discussionmentioning
confidence: 99%
“…The association between polycystic kidney disease and RCC has been well documented [20-22], as well as the association of acquired polycytic kidney disease with renal tumors, which now represent a special type of tumor, already included into the WHO classification [1]. One of the characteristics of those tumors, in addition to the end stage kidney disease, is the abundance of calcium oxalate crystals.…”
Section: Discussionmentioning
confidence: 99%
“…However, no specific type of neoplasm has been descibed to occur in ADPKD. Most common histological subtypes assocated with ADPKD were clear cell RCC, followed by papillary and tubulocystic carcinoma [20-22]. Primary neuroendocrine tumors of the kidney, although rare, have also been reported to most commonly arise in the setting of acquired and congenital abnormalities, including polycystic kidney disease in 2% [23].…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why some studies have not demonstrated any significant statistical support for the association of ADPKD and RCC. However, the majority of papers published on this topic still continue to support the hypothesis of an association [7,12,13].…”
Section: Commentarymentioning
confidence: 99%
“…However, numerous studies have demonstrated that the rates of RCC in ADPKD patients are still higher when adjusted for time spent on RRT and compared with ESRD patients whose kidneys failed due to other causes than ADPKD [10,11,14]. Furthermore, RCC develops in ADPKD patients at much younger ages (average 47 years) and is often bilateral (30%) and multi-centric (25%) [7,13], much higher than found in sporadic RCC with 61 years being their median onset, 2%-6% are bilateral, and only 5% are multi-centric [12,13]. These clinical features of RCC in the ADPKD population are specific and unique, and the increased prevalence could be attributed to the associated ADPKD genetics.…”
Section: Commentarymentioning
confidence: 99%